Progression of myopic maculopathy after treatment of choroidal neovascularization - Farinha, CL (2014)
Purpose: To evaluate the long-term progression of myopic maculopathy and functional outcome after treatment of myopic choroidal neovascularization (CNV) with photodynamic therapy (PDT) and/or intravitreal ranibizumab (IVR). Methods: Retrospective study with a cross-sectional evaluation. Eyes were assigned to 4 groups (PDT, IVR, PDT + IVR, dry myopic maculopathy) and evaluated with best-corrected visual acuity, color fundus photography and spectral-domain optical coherence tomography. Chorioretinal atrophy progression was quantified. Results: Fifty-four eyes were included with a mean follow-up of 80.6 ± 28.0 months. The prevalence of diffuse, patchy and macular atrophy increased during the follow-up, in contrast with tessellated fundus, lacquer cracks and active CNV. Progression of macular atrophy was significant in the 3 treatment groups (p < 0.05) and predictive of visual acuity. It depended on age, degree of myopia and presence of staphyloma, but not on the type of treatment. Conclusions: The long-term functional outcome of eyes with myopic CNV is more dependent on the progression of macular atrophy, and not on the type of treatment.